2020
DOI: 10.3390/nu12113228
|View full text |Cite
|
Sign up to set email alerts
|

Time-Restricted Eating as a Nutrition Strategy for Individuals with Type 2 Diabetes: A Feasibility Study

Abstract: Individuals with type 2 diabetes (T2D) require a long-term dietary strategy for blood glucose management and may benefit from time-restricted eating (TRE, where the duration between the first and last energy intake is restricted to 8–10 h/day). We aimed to determine the feasibility of TRE for individuals with T2D. Participants with T2D (HbA1c >6.5 to <9%, eating window >12 h/day) were recruited to a pre-post, non-randomised intervention consisting of a 2-week Habitual period to establish baseline diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
166
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(175 citation statements)
references
References 57 publications
2
166
1
6
Order By: Relevance
“…Preliminary research identified four hundred and ninety-four articles, including clinical trials, literature reviews and other relevant work. After the exclusion of one hundred and six duplicates, three hundred and eighty-eight articles remained, from which 22 have been finally selected [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. An article was added during the full article reading stage (R15—[ 41 ]), making a total of 23 articles included for analysis (see flow chart in Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary research identified four hundred and ninety-four articles, including clinical trials, literature reviews and other relevant work. After the exclusion of one hundred and six duplicates, three hundred and eighty-eight articles remained, from which 22 have been finally selected [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. An article was added during the full article reading stage (R15—[ 41 ]), making a total of 23 articles included for analysis (see flow chart in Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, one pilot study of an American population of patients with diagnosed MetS [ 34 ] and several small-scale TRE trials in the populations (mainly from the US) with elevated BMI (overweight or obese subjects) [ 25 , 35 , 36 , 37 , 38 , 40 , 41 , 42 , 44 , 45 , 46 ], increased waist circumference (individuals with central obesity) [ 39 , 40 , 43 ], and disorders of glucose metabolism (subjects with prediabetes, high risk of T2DM, and T2D with controlled hyperglycemia (HbA1c < 9%) either by diet or taking ≤ two oral hypoglycemic agents) [ 37 , 39 , 47 ] were conducted. The trials of individuals with metabolic disorders demonstrated that TRE result in several cardiometabolic benefits such as weight loss [ 25 , 34 , 35 , 38 , 39 , 40 , 43 , 44 ] and a decrease in body fat [ 34 , 35 , 36 , 43 , 44 ] and energy intake [ 25 , 34 , 36 , 38 , 44 , 47 ], as well as improved glucose tolerance [ 39 ], insulin resistance [ 37 , 38 , 41 , 44 ], glycemic control [ 35 , 36 , 39 , 41 , …”
Section: Discussionmentioning
confidence: 99%
“…In the pilot study of American patients with MetS, the improvements in body weight and fat, waist circumference, atherogenic lipids, and BP were observed despite no overt attempt to change diet quantity and quality or physical activity [ 34 ]. Moreover, previous TRE trials of subjects with metabolic disorders reported good adherence with TRE for a period up to 16 weeks [ 25 , 34 , 35 , 38 , 43 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations